REVEALING THE ACCOUNTABILITY OF VILLAGE FINANCIAL MANAGEMENT AND REPORTING BEHIND THE VEIL OF LOCAL CULTURAL VALUES - Suhartono Suhartono; Irna Virana; Irmawati Irmawati; Nurbiah Saheba Putri (Universitas Islam Negeri Alauddin Makassar, 2019)
The purpose of this study is to disclouse the implementation of local culture values siri’ na pacce’ and sipakatau sipakainge to management accountability and financial reporting of the village. The value of local culture is a combination of divine values and various values that are formed as the excellence of local culture as well as geographical conditions in the broad context, as past cultural products are continuously Should be made a living. Ethnic Bugis and Makassar Ethnic are two among the four major ethnicities residing in South Sulawesi that has alignment of purpose of life and the value of the values that should be embraced by everyone in social life like siri’ na pacce and sipakatau sipakainga. Research data collected through observation, interviews, and documentation related information. From the results of the study found that the accountability of village financial management and reporting in Bontolebang Village, Bontorappo Village, and Tarowang village of Jeneponto District has been in line with these local cultural values.